PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL GUIDED DISCOVERY LEARNING DI KELAS V - Nurlev Avana; Jamaris Jamaris; Solfema Solfema; Reni Guswita; Sonya Elmanda (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
The background of this research is because of the low learning process and learning outcomes in mathematics by fifth-grade students at SDN 81/II Muara Bungo. This research aims to improve it by using guided discovery learning models. This type of research is classroom action research with two cycles. Each cycle is divided into two meetings. Each meeting is divided into four stages: planning, implementation, observation, and reflection. This research targets the fifth-grade students of SDN 81/II Muara Bungo in the second semester of the 2020/2021 academic year. The results of this research data analysis indicate that the use of guided discovery learning models can improve the process and learning outcomes of fifth-grade mathematics at SD 81/II Muara Bungo. The details of observations made by the teacher in the first cycle resulted in an average score of 85.4%. Then in the second cycle, it produced 93.5% as the excellent category. Then the results of observations made by students in the first cycle obtained the percentage value of 68.2% and 87.4% in the second cycle. And classical completeness in the first cycle, the average value of student learning outcomes was 68.2%, increasing to 90.9% in the second cycle. The conclusion is, using guided discovery learning models can improve the process and results of learning mathematics.